Description of two new species of the genus Devadatta from northern Vietnam and central Laos (Odonata: Devadattidae) - Phan, Quoc Toan; Sasamoto, Akihiko; Hayashi, Fumio (Zootaxa, 2015)
Two new species of the genus Devadatta Kirby, 1890, D. kompieri sp. nov. from northern Vietnam (holotype: male, Mu Cang Chai district, Yen Bai Province) and D. yokoii sp. nov. from central Laos (holotype: male, Vang Vieng, Vientiane Province) are described. These new species are allied to D. ducatrix Lieftinck, 1969, but are distinguished by specific characteristics of their wings and anal appendages. The other Indochinese species are also briefly discussed.